2019
DOI: 10.1021/acsami.9b16067
|View full text |Cite
|
Sign up to set email alerts
|

Light-Guided Surface Plasmonic Bubble Movement via Contact Line De-Pinning by In-Situ Deposited Plasmonic Nanoparticle Heating

Abstract: Precise spatio-temporal control of surface bubble movement can benefit a wide range of applications like high-throughput drug screening, combinatorial material development, microfluidic logic, colloidal and molecular assembly, etc. In this work, we demonstrate that surface bubbles on a solid surface are directed by a laser to move at high speeds (> 1.8 mm/s), and we elucidate the mechanism to be the de-pinning of the three-phase contact line (TPCL) by rapid plasmonic heating of nanoparticles (NPs) deposited in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 45 publications
(102 reference statements)
4
69
0
Order By: Relevance
“…Various theoretical and computational studies of this method were carried out. [ 72,75,80–82 ] In certain cases where laser light is absorbed by preformed particles but not by the substrate, Zhang et al. [ 80 ] showed that the part of the microbubble further away from the substrate is hotter than the part closer to the substrate (Figure 4f).…”
Section: Directed Assembly Of Preformed Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Various theoretical and computational studies of this method were carried out. [ 72,75,80–82 ] In certain cases where laser light is absorbed by preformed particles but not by the substrate, Zhang et al. [ 80 ] showed that the part of the microbubble further away from the substrate is hotter than the part closer to the substrate (Figure 4f).…”
Section: Directed Assembly Of Preformed Materialsmentioning
confidence: 99%
“…(f) Adapted with permission. [ 80 ] Copyright 2019, American Chemical Society. (g) Reproduced with permission.…”
Section: Directed Assembly Of Preformed Materialsmentioning
confidence: 99%
See 3 more Smart Citations